2022
DOI: 10.3855/jidc.15603
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance rate of COVID-19 vaccination and its predictors in Egypt: An online survey

Abstract: Introduction: Public acceptance, understanding, and trust are some significant challenges facing COVID-19 vaccine coverage. Our study objective was to assess the acceptance rate of COVID-19 vaccination and its predictors among the Egyptian adult population. Methods: An online survey was conducted on 1,053 participants from six randomly selected governorates in Egypt between March and April 2021 using an Arabic self-administrated questionnaire, developed using the Google Form App. Results: Out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Concerns about safety as well as general lack of trust in the vaccines were the main reasons for vaccine hesitancy among healthcare workers in Sudan and Iraq [ 11 , 12 ]. Lack of trust in vaccine effectiveness and fear of side effects were the main reasons for refusing to be vaccinated also among the general population [ 9 , 13 , 14 , 15 ], while the belief in the effectiveness and benefits associated with the COVID-19 vaccination was the main reason for vaccine acceptance [ 14 , 16 ]. Beliefs associated with vaccination status are also the core determinants of vaccination status in Syria.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about safety as well as general lack of trust in the vaccines were the main reasons for vaccine hesitancy among healthcare workers in Sudan and Iraq [ 11 , 12 ]. Lack of trust in vaccine effectiveness and fear of side effects were the main reasons for refusing to be vaccinated also among the general population [ 9 , 13 , 14 , 15 ], while the belief in the effectiveness and benefits associated with the COVID-19 vaccination was the main reason for vaccine acceptance [ 14 , 16 ]. Beliefs associated with vaccination status are also the core determinants of vaccination status in Syria.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a large body of evidence stemming from the Middle East, North Africa, and Eastern Mediterranean region has also documented the link between vaccine beliefs and vaccination status. A study about vaccination among healthcare workers in Egypt, for example, found that the reasons for vaccine acceptance revolved around safety and effectiveness, while fear of side effects was the main reason for vaccine hesitancy [ 17 ]. Concerns about safety as well as a general lack of trust in the vaccines, were the main reason for vaccine hesitancy among healthcare workers in Sudan and Iraq [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about safety as well as a general lack of trust in the vaccines, were the main reason for vaccine hesitancy among healthcare workers in Sudan and Iraq [ 18 , 19 ]. Lack of trust in vaccine effectiveness and fear of side effects were the also main reasons for refusing to be vaccinated among the general population [ 17 , 20 , 21 , 22 ], while the belief in the effectiveness and benefits associated with the COVID-19 vaccination were the main reasons for vaccine acceptance [ 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Highly reliable clinical evidence derived from randomized clinical trials confirmed that Sinopharm vaccine reduced the incidence of symptomatic COVID-19 [ 10 ]. Regrettably, the acceptance and immunization rates for COVID-19 vaccines in Egypt are reportedly low [ [11] , [12] , [13] ]. The present study aimed to compare the rate of reinfection after two and three doses of Sinopharm COVID-19 vaccine in HD patients.…”
Section: Introductionmentioning
confidence: 99%